In the limelight: Utilizing clinical simulations to enhance music teacher education. (April 2019) - Dotger, Benjamin; Dekaney, Elisa; Coggiola, John
In field placements, preservice music teachers (PMTs) rarely have the opportunity to communicate one-to-one with parents/caregivers. Situated within a clinical environment, this study examines how PMTs engage with a concerned mother whose daughter did not have a successful audition for a school musical. We approach this inquiry from a unique perspective, drawing on a pedagogy comprehensively used to prepare physicians, and using it with our own PMTs. We begin by outlining medical education's use of simulations with standardized patients to prepare future medical professionals to effectively engage with patients. Then, we turn attention to the music simulation designed for our PMTs, the challenges they all faced from the same concerned mother, and the data resulting from their face-to-face conversations. Implications center on the use of clinical simulations as a pedagogy to enhance music teacher preparation.